2011
DOI: 10.1007/s10529-011-0685-6
|View full text |Cite
|
Sign up to set email alerts
|

Highly regioselective synthesis of undecylenic acid esters of purine nucleosides catalyzed by Candida antarctica lipase B

Abstract: Regioselective undecylenoylation of purine nucleosides as potential dual prodrugs was achieved by Candida antarctica lipase B using adenosine as a model reactant. The optimum organic solvent, molar ratio of vinyl ester to nucleoside, enzyme dosage, reaction temperature and molecular sieve amount were anhydrous THF, 5:1, 20 U/ml, 45°C and 75 mg/ml, respectively. Under the optimum conditions, the initial reaction rate, yield and 5'-regioselectivity were 1.1 mM/h, 90% and >99%, respectively. The enzymatic acylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The lipase activity was was assayed with p -nitrophenyl acetate hydrolysis as a model reaction [19] . In a typical experiment, 0.6 mL phosphate buffer (50 mM, pH 8.0) containing 0.1 mL p -nitrophenyl acetate (10 mM dissolve in 2-propanol) and the enzyme was incubated at 45°C and 200 rpm for 20 min, then stopped by adding 0.1 M Na 2 CO 3 solution.…”
Section: Methodsmentioning
confidence: 99%
“…The lipase activity was was assayed with p -nitrophenyl acetate hydrolysis as a model reaction [19] . In a typical experiment, 0.6 mL phosphate buffer (50 mM, pH 8.0) containing 0.1 mL p -nitrophenyl acetate (10 mM dissolve in 2-propanol) and the enzyme was incubated at 45°C and 200 rpm for 20 min, then stopped by adding 0.1 M Na 2 CO 3 solution.…”
Section: Methodsmentioning
confidence: 99%
“…The enzyme esterification activity was determined according to the method [14] . The specific activities of CAL-B, TLL, RML, CRL, PCL and PRL were 2.5, 0.21, 0.27, 0.68, 0.13 and 2.71 U/mg, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25][26] Many works had been reported on the biocatalysis of purine nucleoside esters. The lipase from C. antarctica was used to catalyze 5 0 -O-acylated adenosines by V. Gotor et al 27 In this work, the target products were obtained in DMSO for 18-24 h. Zhao et al reported that regioselective acylation of cytarabine catalyzed by Pseudomonas uorescens whole-cells was obtained aer 144 h. 28 Regioselective undecylenoylation of adenosine catalyzed by Candida antarctica lipase B needed 23 h. 29 These works are of great signicance for the biocatalysis of purine nucleoside esters. As we can see, biocatalytic method of purine nucleoside esters sometimes required long reaction times or toxic solvents.…”
Section: Introductionmentioning
confidence: 92%